Analysis of Superbuilding Planning and Loading in Bridge Construction - Jason Angelo Ong; Andri Irfan Rifa'i (Fakultas Teknik Sipil dan Perencanaan, 2025)
Bridges are a facility that is often and most needed in every region. Generally, a bridge is a structure formed from steel structures stretching between two areas, either connecting an island or as access to a location. Bridges are the most common and easy-to-find structures. In Indonesia, you can find many bridges, especially in every region. In general, bridges in Indonesia function as links between islands, which can help the economy of residents on the islands. Based on calculations in the structural planning of the upper bridge, the dead load loading value was 0.88307 t/m, and the live load was 18.518 t/m. Planning in vehicle floor mechanics where dead load is obtained: 0.41535 t/m and live load: 6.4581 t/m.